2015
DOI: 10.3133/ofr20151020
|View full text |Cite
|
Sign up to set email alerts
|

Mercury and selenium contamination in waterbird eggs and risk to avian reproduction at Great Salt Lake, Utah

Abstract: For more information on the USGS-the Federal source for science about the Earth, its natural and living resources, natural hazards, and the environment-visit http://www.usgs.gov or call 1-888-ASK-USGS For an overview of USGS information products, including maps, imagery, and publications, visit http://www.usgs.gov/pubprodTo order this and other USGS information products, visit http://store.usgs.gov Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…For marsh wrens ( Cistothorus palustris ) and white‐faced ibises ( Plegadis chihi ) breeding at Great Salt Lake (UT, USA), Ackerman et al found statistically significant differences in Hg concentrations between opportunistically collected eggs from abandoned nests and randomly collected eggs from successful nests (termed “surrogate eggs”). However, the difference in Hg concentration in the 2 groups was small (<0.15 mg/kg), and the eggs consistently contained more Se than Hg on a molar basis, which may ameliorate potential Hg‐related effects .…”
Section: Literature Review Resultsmentioning
confidence: 99%
“…For marsh wrens ( Cistothorus palustris ) and white‐faced ibises ( Plegadis chihi ) breeding at Great Salt Lake (UT, USA), Ackerman et al found statistically significant differences in Hg concentrations between opportunistically collected eggs from abandoned nests and randomly collected eggs from successful nests (termed “surrogate eggs”). However, the difference in Hg concentration in the 2 groups was small (<0.15 mg/kg), and the eggs consistently contained more Se than Hg on a molar basis, which may ameliorate potential Hg‐related effects .…”
Section: Literature Review Resultsmentioning
confidence: 99%
“…We collected 549 eggs from 549 nests of 23 avian species at several locations around Great Salt Lake, Utah, USA, between 10 May and 9 July 2011 (Table ). We visited each nest only once and randomly selected 1 egg for collection as part of a larger study on egg contaminant concentrations around Great Salt Lake . While in the field, we stored eggs in egg cartons on ice.…”
Section: Methodsmentioning
confidence: 99%
“…Biomagnification factors for Se and Hg in brine flies living in oxic environments are modest (Hg -2.2X; Se -1.2X; Wurtsbaugh et al, 2011). Nevertheless, recent analysis of GSL waterfowl revealed that their eggs have Se and Hg levels exceeding toxicity benchmarks or regulatory standards (Ackerman et al, 2015). Additionally, Hg concentrations in three local duck species exceed human dietary thresholds, leading Utah to issue consumption advisories (Utah Department of Environmental Quality, 2019).…”
Section: Spatial Distribution and Toxicity Of Metalsmentioning
confidence: 99%